2020
DOI: 10.1021/acsami.0c04489
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Morphology Effect on the Negative Capacitance and Large Ideality Factor in Perovskite Light-Emitting Diodes

Abstract: Perovskite light-emitting diodes have almost reached the threshold for potential commercialization within a few years of research. However, there are still some unsolved puzzles such as large ideality factor and the presence of large negative capacitance especially at the low-frequency regime yet to be addressed. Here, we have fabricated a methylammonium lead tri-bromide perovskite n–i–p structure for light-emitting diodes from a smooth and textured emissive layer and demonstrated for the first time that these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 70 publications
0
45
0
Order By: Relevance
“…2f portrays the Nyquist plot of the PeLEDs measured under an applied bias of 4 V, revealing that the PeLEDs addressed with AT possess a smaller radius than that of the pristine device, which further indicates the reduced charge transfer resistance due to ATinduced interface engineering. 6,31 To further estimate the relationship between the device performance and interface modification, space-charge-limited-current (SCLC) measurements were performed to explore the defect density. 15,[32][33][34] The current density-voltage ( J-V) curves of the hole-only devices with an architecture of ITO/pure or AT-modified PEDOT:PSS/perovskite/molybdenum oxide (MoOx)/silver (Ag) are depicted in Fig.…”
Section: Device Performancementioning
confidence: 99%
“…2f portrays the Nyquist plot of the PeLEDs measured under an applied bias of 4 V, revealing that the PeLEDs addressed with AT possess a smaller radius than that of the pristine device, which further indicates the reduced charge transfer resistance due to ATinduced interface engineering. 6,31 To further estimate the relationship between the device performance and interface modification, space-charge-limited-current (SCLC) measurements were performed to explore the defect density. 15,[32][33][34] The current density-voltage ( J-V) curves of the hole-only devices with an architecture of ITO/pure or AT-modified PEDOT:PSS/perovskite/molybdenum oxide (MoOx)/silver (Ag) are depicted in Fig.…”
Section: Device Performancementioning
confidence: 99%
“…The capacitive response of PSC can be divided into three distinct frequency regimes namely, low (f < 100 Hz), intermediate (100 Hz < f < 0.1 MHz), and high (f > 0.1 MHz). 20 The high and intermediate frequency is often related to the chemical capacitance and dipole contributions, 21 respectively, whereas the low frequency response represents the electrode polarization due to the accumulation of charges 22 and ion migration. 23 As shown in Figure 1, the high frequency capacitance does not change with light intensity hence, it can be treated as a geometric capacitance.…”
Section: Resultsmentioning
confidence: 99%
“…Good perovskite film morphology does not always refer to a smooth, pinhole-free, and compact perovskite film but is also expected to have favorable interfacial electrical properties. Using the antisolvent treatment and controlling the dripping delay, Kumar et al demonstrated that film morphology can be tuned by tuning the route of the crystal growth, and thus, both the smooth and the textured perovskite film can be designed accordingly ( Kumar R. et al, 2020 ). These textured films show better charge injection/extraction properties at the perovskite/electron transport layer interface in the perovskite light-emitting diode as compared to the archetypical smooth films.…”
Section: Introductionmentioning
confidence: 99%